Laparoscopic removal of a 40-cm paratubal cyst in a morbidly obese patient - Luay Ibrahim Abu Atileh; Duaa Dahbour; Hasan Hammo; Mai Abdullattif (Gynecology and Minimally Invasive Therapy, 2020)
Paratubal cysts (PTCs) are remnants of the paramesonephric or the mesonephric ducts that are present during embryogenesis. They are mostly benign; however, malignancy has been described. The incidence of PTCs is estimated to be 5%–20% of all adnexal masses. They can present in any age group but most commonly the third or fourth decades. Huge PTCs exceeding 10–15 cm in diameter are considered rare and challenging, as only a few cases have been reported that describe complete laparoscopic excision. A simple asymptomatic PTC can be managed expectantly; however, surgery is mandatory if the cyst is huge, complicated, or causes severe symptoms. In this article, we describe a laparoscopic removal of a 40-cm PTC in a 32-year- old woman, as the largest PTC in literature that was removed by laparoscopy.